2017
DOI: 10.1152/ajpgi.00448.2016
|View full text |Cite
|
Sign up to set email alerts
|

Human-derived gut microbiota modulates colonic secretion in mice by regulating 5-HT3 receptor expression via acetate production

Abstract: Serotonin [5-hydroxytryptamine (5-HT)], an important neurotransmitter and a paracrine messenger in the gastrointestinal tract, regulates intestinal secretion by its action primarily on 5-HT and 5-HT receptors. Recent studies highlight the role of gut microbiota in 5-HT biosynthesis. In this study, we determine whether human-derived gut microbiota affects host secretory response to 5-HT and 5-HT receptor expression. We used proximal colonic mucosa-submucosa preparation from age-matched Swiss Webster germ-free (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 39 publications
3
54
0
Order By: Relevance
“…In addition to its characteristic as an important neurotransmitter, 5‐HT is also a potent secretagogue and a significant regulatory factor in the digestive tract (Bhattarai et al., ). The majority (90%) of 5‐HT in the body is released from the enterochromaffin (EC) cells and is derived from the hydroxylation of the dietary L‐ Trp (Gershon & Tack, ).…”
Section: Tryptophan Microbiota and The Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its characteristic as an important neurotransmitter, 5‐HT is also a potent secretagogue and a significant regulatory factor in the digestive tract (Bhattarai et al., ). The majority (90%) of 5‐HT in the body is released from the enterochromaffin (EC) cells and is derived from the hydroxylation of the dietary L‐ Trp (Gershon & Tack, ).…”
Section: Tryptophan Microbiota and The Immune Systemmentioning
confidence: 99%
“…At least seven different families of 5‐HT receptors and fourteen receptor subtypes have been identified (Bhattarai et al., ). Among them, the type 3 serotonin receptor (5‐HT3R) and 5‐HT4R are involved in the host 5‐HT biosynthesis and GI transit modulations via the gut microbiota (Kashyap et al., ); thus, these two receptors are pivotal in regulating intestinal secretion.…”
Section: Tryptophan Microbiota and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific bile acids, such as deoxycholate and chenodeoxycholate, can stimulate intestinal chloride secretion 97, 98 which is accompanied by water. SCFAs, like bile acids, are important intraluminal determinants of mucus and water secretion through effects on sodium and water influx 99 , duodenal bicarbonate secretion 100 , and colonic epithelial 5-HT 3 receptor expression 101 .…”
Section: Effect Of the Gut Microbiota On Host Physiologymentioning
confidence: 99%
“…Bhattarai et al [62] analysed serotonin-sensitive ion secretion in GF mice in comparison with mice colonised with human gut microbiota, and showed that GF mice had a notably greater secretory response to serotonin than their human gut microbiota controls, indicating that the presence of gut microbiota may modulate the secretory response to 5-HT.…”
Section: Gut-microbiota and Serotonin Metabolismmentioning
confidence: 99%